Nonlinear Mid‐Infrared Metasurface based on a Phase‐Change Material. Issue 3 (1st February 2021) - Yue, Fuyong; Piccoli, Riccardo; Shalaginov, Mikhail Y.; Gu, Tian; Richardson, Kathleen A.; Morandotti, Roberto; Hu, Juejun; Razzari, Luca
Abstract: The mid‐wave infrared (MWIR) spectral region (3–5 µm) is important to a vast variety of applications in imaging, sensing, spectroscopy, surgery, and optical communications. Efficient third‐harmonic generation (THG), converting light from the MWIR range into the near‐infrared, a region with mature optical detection and manipulation technologies, offers the opportunity to mitigate a commonly recognized limitation of current MWIR systems. In this work, the possibility of boosting THG in the MWIR through a metasurface design is presented. Specifically, a 30‐fold enhancement in a highly nonlinear phase‐change material Ge2 Sb2 Se4 Te1 (GSST) is demonstrated by patterning arrays of subwavelength cylinders supporting a magnetic dipolar resonance. The unprecedented broadband transparency, large refractive index, and remarkably high nonlinear response, together with unique phase‐change properties, make GSST‐based metasurfaces an appealing solution for reconfigurable and ultra‐compact nonlinear devices operating in the MWIR. Abstract : A 30‐fold enhancement of third harmonic generation from the mid‐infrared to the optical telecom band is demonstrated in the highly nonlinear phase‐change material Ge2 Sb2 Se4 Te1 through a metasurface design. The broadband transparency and remarkably large nonlinear response of such phase‐change metasurfaces make them a promising platform for the next generation of reconfigurable upconverting metadevices operating in the mid‐infrared.